2019
DOI: 10.20944/preprints201901.0167.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Market Risk and Financial Performance of Non-financial Companies Listed on the Moroccan Stock Exchange

Abstract: This study examines the effect of market risk on the financial performance of 31 non-financial companies listed on the Casablanca Stock Exchange (CSE) over the period 2000-2016. We utilize three alternative variables to assess financial performance, namely return on assets, return on equity and profit margin. Next, we use the degree of financial leverage, the book-to-market ratio, and the gearing ratio as market risk variables. Besides, we employ the pooled OLS model, the fixed effects model, the random-effect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…The result of hypothesis test revealed an insignificant negative effect of book-to-market ratio (BMR) on stock return of financial service firms with a coefficient of -0.0319 and p-value of 0.131 at 5% significance level. The result obtained from the regression estimators supported the study of Agbam et al (2018), though the study of Gautam (2017) and Kassi et al (2019) revealed a significant negative effect. However, the result did not support the study of Morelli (2017) and Akwe et al (2018) which found a positive effect of book-to-market ratio on stock return.…”
Section: Hypotheses Testingsupporting
confidence: 85%
See 3 more Smart Citations
“…The result of hypothesis test revealed an insignificant negative effect of book-to-market ratio (BMR) on stock return of financial service firms with a coefficient of -0.0319 and p-value of 0.131 at 5% significance level. The result obtained from the regression estimators supported the study of Agbam et al (2018), though the study of Gautam (2017) and Kassi et al (2019) revealed a significant negative effect. However, the result did not support the study of Morelli (2017) and Akwe et al (2018) which found a positive effect of book-to-market ratio on stock return.…”
Section: Hypotheses Testingsupporting
confidence: 85%
“…Empirical studies have provided measures or indicators of market risk to include firm specific variables of book-to-market ratio which is defined as net total assets or shareholders fund to market capitalization (Kassi, Rathnayake, Louembe & Ding, 2019;Chen et al,2010;Agbam, Anyamaobi & Okon, 2018;Gautam, 2017;Morelli, 2007;Akwe, Garba & Dang 2018); net interest margin defined as net interest income to total assets or average earning asset (Chaudhry et al, 2008;Badawi, 2017;Muriithi, Muturi & Waweru, 2016;Murazi & Usman, 2016). Other empirical measures of market risk include interest rate risk defined in terms of treasury bill or commercial paper rates (Belke & Poliet, 2004;Mwaurah, 2019), monetary policy rate (Okpara, 2010); foreign exchange risk defined as percentage change in a country's currency rate to a base rate (Mwaurah, 2019); inflation rate defined change in general price level of goods and services on a year-to-year basis (Alagided & Panagiotidis, 2006;Daferighe & Aje, 2009); monetary policy rate defined as the interest rate issued by a central or reserve bank of a country (Abbass, Song, Shah & Aziz, 2019).…”
Section: Figure 1 Source: Field Work (2020)mentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of "capital structure" or "financial structure" relates to financing issues. In line with the related literature (Friend & Lang, 1988;Kassi et al, 2019;Lin et al, 2008), we exclude trade credit for several reasons. First, we focus on financial leverage given that it produces debt interest and its tax deductibility is affected by the thin capitalization rule studied in this paper (Ampenberguer et al, 2013;Clemente & Sogorb, 2016).…”
Section: Dependent Variablementioning
confidence: 99%